Recurrence rates of Barrett’s esophagus and dysplasia in patients successfully treated with radiofrequency ablation vs. cryoballoon ablation: a comparative study - Sachdeva, Karan; Chandi, Paras Singh; Verma, Anjul; Dierkhising, Ross; Codipilly, D. Chamil; Leggett, Cadman L.; Trindade, Arvind J.; Iyer, Prasad G. (Endoscopy, 2025)
Endoscopic eradication therapy (EET) is recommended for the management of dysplastic Barrett’s esophagus (BE) and intramucosal adenocarcinoma. Both radiofrequency (RFA) and cryoballoon ablation (CBA) can induce complete remission of intestinal metaplasia (CRIM). We aimed to compare long-term durability following CRIM in patients treated with RFA vs. CBA.We conducted a retrospective cohort study to analyze patient outcomes following EET with RFA or CBA at two referral centers. We measured and compared the recurrence rate of BE, with or without dysplasia, after CRIM, using Cox proportional hazard models and propensity score-matched analyses. Our secondary aim was to identify predictors of recurrence.681 patients who achieved CRIM were included (RFA 610; CBA 71), with median follow-up of 4.1 years and 4.4 years following RFA and CBA, respectively. A multivariable model revealed a higher risk of any recurrence with RFA (hazard ratio [HR] 2.19, 95%CI 1.18–4.06; P = 0.01), but not dysplastic recurrence (HR 0.88, 95%CI 0.39–1.97; P = 0.75). However, a comparable risk of “any recurrence” was observed after excluding intestinal metaplasia of the gastroesophageal junction (HR 1.18, 95%CI 0.61–2.30; P = 0.62). Propensity score-matched analysis (54 cases in each group) showed that the two groups had comparable recurrence risk. Baseline maximum BE length was associated with a higher risk of any recurrence (HR 1.07; P<0.001) and dysplastic recurrence (HR 1.11; P = 0.001).The rates of any BE recurrence and dysplastic recurrence were comparable with the two modalities in this nonrandomized study.